PENEGAKAN HUKUM TERHADAP PENAMBANGAN BATUBARA ILEGAL DITINJAU DARI PERSPEKTIF HUKUM - Ukut Ukut (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Nowadays mining activities have been highly developed. The results obtained are also very useful for income for the community, especially for the miners. However, the problem that must be considered by the government is the problem of illegal mining. Illegal mining is carried out without permission, operational procedures, and regulations from the government. This makes a loss to the country. These Unlicensed Mining Issues are factors that cause uncontrolled environmental damage and other problems. Mining activities without permits/ illegal mining cannot be separated from several factors that underlie the approval.This type of research used by the author is normative or doctrinal legal research whose explanation is normative legal research the other name is doctrinal legal research which is also referred to as library research or document study. The approach used in this paper is the statute approach and statute approach. Conceptual Approach.Inhibiting Factors in Legal Application of Illegal Coal Mining Seen From a Mental Perspective, which is faced with problems regarding the socio-economic conditions of the mining community, the rampant practice, illegal mining is also caused by the lack of public knowledge of mining laws and regulations, as well as the inherent culture of customary law. Keywords : Illegal Mining, Law Enforcement, Legal Perspective